ETHICAL PRINCIPLES OF REALIZATION OF THE RIGHT OF OWNERSHIP - Patsurkivskyi, Yurii (Europian journal of Law and Public Administration, 2018)
In the following article are examined theoretical and practical aspects of realization of civil laws. Basic principles of realization of civil laws are principles of freedom of realization of equitable rights and principle of observance of the set limits of realization of civil laws. It is suggested to understand other principles of realization of civil laws (honesty, cleverness, accordance of setting of right, solidarity of members’ interests of legal relationships) in quality of limits of realization of right. The article is dedicated to research of problem questions of realization of equitable civil rights and duties, and also determination of their intercommunication. The different aspects of intercommunication of realization of civil laws and implementation of duties are analyzed. The theoretical and practical aspects of discretion of subjects of civil legal relationships are examined during realization of evaluation concepts in a civil law. Basic principle is subjective interest during realization of discretion of subject. An important role is played by an estimation carried out by a subject at realization of maintenance of evaluation concept. This estimation represents as vital experience of subject so degree of realization to them of maintenance of evaluation concept in a civil law. The problem of the realization of law was and until now is considered ambiguous and became the subject of lively scientific discussions. The right is an endless work not only of state power, but of the whole people, and all life is a reflection of the unceasing struggle and work of the whole people, which clearly outlines the activities of the people in the field of economic and intellectual production. Taking into account the contradictory nature of many theoretical issues of the realization of law, as well as their exceptional complexity, lawyers have repeatedly turned to the analysis of the legal nature and the features associated with the implementation of law. However, to date, the problem of realizing law in the field of private law is one of the less investigated areas in legal science, which have not found the proper theoretical and practical solutions. All this in aggregate determines the relevance and choice of the topic of my scientific research.
Keywords: Principles of realization of rights; principles of realization of civil laws; honesty; cleverness; justice; buse of law,